The Landscape Genetic Signature of Pollination by Trapliners: Evidence From the Tropical Herb, Heliconia tortuosa - Torres-Vanegas, Felipe; Hadley, Adam S.; Kormann, Urs G.; Jones, Frank Andrew; Betts, Matthew G.; Wagner, Helene H. (Frontiers in Genetics, 2019)
Animal-mediated pollination is essential for the maintenance of plant reproduction, especially in tropical ecosystems where pollination networks have been thought to have highly generalized structures. However, accumulating evidence suggests that not all floral visitors provide equally effective pollination services, potentially reducing the number of realized pollinators and increasing the cryptic specialization of pollination networks. Thus, there is a need to understand how different functional groups of pollinators influence pollination success. Here we examined whether patterns of contemporary pollen-mediated gene flow in Heliconia tortuosa show a landscape genetic signature consistent with the foraging strategy of its territorial or traplining hummingbird pollinators. Territorial hummingbirds defend clumps of flowers and are expected to transfer pollen locally. In contrast, traplining hummingbirds forage across long-distances and repeatedly visit particular plants, thereby increasing pollen flow among forest fragments. If trapliners indeed visit the same plants repeatedly along their regular routes, this could lead to a situation where neighboring plants sample genetically distinct pollen pools. To test this hypothesis, we genotyped 720 seeds and 71 mother plants from 18 forest fragments at 11 microsatellite loci. We performed TwoGener analysis to test pollen pool genetic differentiation within sites (among neighboring plants within the same forest fragment: ΦSC) and between sites (among forest fragments: ΦCT). We found strong, statistically significant pollen pool genetic differentiation among neighboring mother plants (ΦSC = 0.1267), and weaker, statistically significant differentiation among sites (ΦCT = 0.0735). These patterns are a landscape genetic signature of the foraging strategy of traplining hummingbirds, where repeatable, long-distance, and high-fidelity routes transfer pollen among particular plants. Although H. tortuosa is also visited by territorial hummingbirds, our results suggest that these pollinators do not contribute substantially to successful pollination, highlighting differences in realized pollination efficiency. This cryptic reduction in the number of realized pollinators potentially increases the vulnerability of pollination success to the decline of populations of traplining hummingbirds, which have been shown to be sensitive to forest fragmentation. We conclude that maintaining habitat connectivity to sustain the foraging routes of trapliners may be essential for the maintenance of pollen-mediated gene flow in human-modified landscapes.